Expression and Characterization of Alkaline Phosphatase from Cobetia amphilecti KMM 296 in Transiently Transformed Tobacco Leaves and Transgenic Calli - Peter Adeolu Adedibu; Yulia Aleksandrovna Noskova; Yulia Anatolievna Yugay; Daria Mikhailovna Ovsiannikova; Elena Anatolievna Vasyutkina; Olesya Dmitrievna Kudinova; Valeria Petrovna Grigorchuk; Yury Nikolaevich Shkryl; Liudmila Aleksandrovna Tekutyeva; Larissa Anatolievna Balabanova (Plants)
Alkaline phosphatase (ALP) of the PhoA family is an important enzyme in mammals, microalgae, and certain marine bacteria. It plays a crucial role in the dephosphorylation of lipopolysaccharides (LPS) and nucleotides, which overstimulate cell signaling pathways and cause tissue inflammation in animals and humans. Insufficient ALP activity and expression levels have been linked to various disorders. This study aims to produce recombinant ALP from the marine bacterium Cobetia amphilecti KMM 296 (CmAP) in transformed leaves and calli of Nicotiana tabacum and to elucidate the influence of the plant host on its physical and chemical properties. N. tabacum has proven to be versatile and is extensively used as a heterologous host in molecular farming. The alp gene encoding for CmAP was cloned into the binary vectors pEff and pHREAC and transformed into N. tabacum leaves through agroinfiltration and the leaf disc method for callus induction using Agrobacterium tumefaciens strain EHA105. Transformed plants were screened for recombinant CmAP (rCmAP) production by its enzymatic activity and protein electrophoresis, corresponding to 55 kDa of mature CmAP. A higher rCmAP activity (14.6 U/mg) was detected in a homogenate of leaves bearing the pEFF-CmAP construct, which was further purified 150-fold using metal affinity, followed by anion exchange chromatography. Enzymatic activity and stability were assessed at different temperatures (15–75 °C) and exposure times (≤1 h), with different buffers, pHs, divalent metal ions, and salt concentrations. The results show that rCmAP is relatively thermostable, retaining its activity at 15–45 °C for up to 1 h. Its activity is highest in Tris HCl (pH 9.0–11.0) at 35 °C for 40 min. rCmAP shows higher salt-tolerance and divalent metal-dependence than obtained in Escherichia coli. This can be further explored for cost-effective and massively scalable production of LPS-free CmAP for possible biomedical and agricultural applications.